2014
DOI: 10.1007/s00467-013-2693-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of urinary TIMP1 and MMP9 levels in predicting vesicoureteral reflux in neonates with antenatal hydronephrosis

Abstract: Evaluation of urinary levels of MMP9, or the MMP9/Cr, MMP9/TIMP1, or MMP9/TIMP1/Cr ratios may help us to differentiate the newborns with hydronephrosis and VUR from those without reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Urinary biomarkers are candidates for assessment of kidney injury and have been studied widely for this purpose [ 9 , 10 ]. Theoretically, these markers could be used for the early diagnosis of kidney damage in cases with obstruction [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Urinary biomarkers are candidates for assessment of kidney injury and have been studied widely for this purpose [ 9 , 10 ]. Theoretically, these markers could be used for the early diagnosis of kidney damage in cases with obstruction [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abedi and Mohammadjafari [ 45 ] postulated that urinary MMP-9 and TIMP-1 may be markers of renal scarring in children with urinary tract infections. Other authors [ 46 ] suggested the usefulness of the measurement of urinary MMP-9 excretion and the urinary MMP-9/TIMP-1 ratio for the prediction of vesicoureteral reflux in neonates with antenatal HN. Tian et al [ 47 ] reported that urinary MMP-9 and TIMP-1 may be noninvasive biomarkers in children with UPJO.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MMP9, MMP9/Cr, MMP9/TIMP1, and MMP9/TIMP1/Cr ratios were higher in patients with VUR than in those without VUR. Based on these results, the authors discussed the use of screening tests for the presence of VUR in neonates with hydronephrosis to reduce their exposure to radiation, as in VCUG 40) . Other studies suggests that MMP9 and TIMP1 could be used as biomarkers to predict renal scars in children with UTIs 41,42) .…”
Section: Wwwchikdorgmentioning
confidence: 99%